Isolation and characterization of type IV group B Streptococcus capsular polysaccharide. - Wessels, M R (1989)
An antigenically distinct serotype, type IV, has recently been added to the recognized serotypes of group B streptococci (GBS). We isolated and purified the capsular polysaccharide antigen from a prototype type IV GBS strain. The type IV capsular polysaccharide formed a precipitin line with rabbit antiserum to type IV GBS organisms but not with antiserum to organisms of GBS serotype Ia, Ib, II, or III. Enzyme-linked immunosorbent assay inhibition experiments showed no cross-reaction between type IV antiserum and other GBS serotypes. Capsular polysaccharide released from the bacterial cells with mutanolysin and that isolated from the culture supernatant had similar elution profiles on Sepharose CL-6B, with a Kav of 0.30 and an estimated Mr of 200,000. The purified type IV polysaccharide was found to contain galactose, glucose, N-acetylglucosamine, and N-acetylneuraminic acid (sialic acid) as exclusive sugars. The polysaccharide contained 23% (by weight) sialic acid and galactose, glucose, and N-acetylglucosamine in a relative ratio of (1):1.10:0.55. These results are compatible with a repeating structure of six monosaccharide residues containing galactose, glucose, N-acetylglucosamine, and sialic acid in a molar ratio of 2:2:1:1. Unlike type Ia, II, and III GBS polysaccharides, desialylation of the type IV polysaccharide produced an antigen which formed a line of identity with the native type IV antigen in double diffusion in agar against homologous antiserum. This result suggests that sialic acid is not as critical to the immunodeterminant structure of the type IV antigen as it is for other GBS capsular types.